PEMANFAATAN TOOL ARTIFICIAL INTELLIGENCE (AI) CHATGPT UNTUK OPTIMALISASI PROSES ASESMEN PEMBELAJARAN - Najaf, Abdul Rezha Efrat; Agussalim, Agussalim; Sihananto, Andreas Nugroho (Universitas Sanata Dharma, 2025)
In the era of Society 5.0, education must adopt technology to improve the quality of learning, especially by educators. Technology brings significant changes, with people becoming more aware of the importance of technology skills. Every curriculum requires assessment to evaluate the success of learning, provide an overview of student achievement, and identify areas for improvement. The use of AI tools in student assessment improves the efficiency and quality of learning, allowing for faster and more specific feedback. AI also helps students identify their weaknesses more quickly and work on improving them. The AI training was attended by 18 teachers, starting with registration and followed by AI introduction materials and evaluation training during the learning process. The participants were also accompanied directly to observe their knowledge and skills. The training ended with a posttest to measure participants' understanding. As a result, all participants completed the task, showing a good understanding of the material. The achievement of the objectives demonstrates the success of this training and the utilization of information technology, particularly ChatGPT AI tools, in the learning assessment process. The optimal use of AI requires continuous training for teachers.